Productivity growth and inflation: A multi-country study - Vincent Hogan; Hongmei Zhao (University College Dublin, UCD School of Economics, 2006)
Ball and Moffitt (2001) present a theory implying that the gap between productivity and wage aspirations can shift the traditional Phillips Curve. We examine their theory within the OECD. The results show that there is no clear cross country evidence for the theory. Although Ball and Moffitt's model works well in the U.S., it cannot, in general, be applied to other OECD countries. The time- varying NAIRU can better explain the economic performance for the OECD overall, and the UK in particular, during the late 1990s. In Germany, traditional Phillips Curve still kept its explanatory power during this period.
hdl:10197/332
Keywords: 330